Endoglin aggravates peritoneal fibrosis by regulating the activation of TGF-β/ALK/Smads signaling - Huang, Qian; Xiao, Rui; Lu, Jing; Zhang, Yao; Xu, Liang; Gao, Jie; Sun, Jing; Wang, Haiping (Frontiers in Pharmacology, 2022)
Background: Peritoneal fibrosis (PF) is an intractable complication in patients on long-term peritoneal dialysis (PD). Transforming growth factor-β (TGF-β) is a key pro-fibrogenic factor involved in PD-associated PF, and endoglin, as a coreceptor for TGF-β, plays a role in balancing the TGF-β signaling pathway. Here, we investigated whether endoglin could be a potential therapeutic target for PF. Methods:In vivo, we established PF model in SD rats by daily intraperitoneal injection of peritoneal dialysis fluids (PDF) containing 4.25% glucose for 6 weeks and downregulated endoglin expression by tail vein injection of AAV9-ENG on day 14 to assess the effect of endoglin on peritoneal morphology and markers related to fibrosis, angiogenesis, and epithelial-mesenchymal transition (EMT). In vitro, we treated human peritoneal mesothelial cells (HPMCs) transfected with ENG siRNA in high glucose medium to explore the potential mechanism of endoglin in PF. Results: Compared to control group, continuous exposure to biologically incompatible PDF induced exacerbated PF, accompanied by a significant increase in endoglin expression. Conversely, knockdown of endoglin ameliorated peritoneal injury characterized by increased peritoneal thickening and collagen deposition, angiogenesis, as well as EMT. Consistently, HPMCs cultured in high glucose medium underwent the EMT process and exhibited over-expression of fibronectin, collagen type I, vascular endothelial growth factor (VEGF), whereas these aforementioned alterations were alleviated after ENG siRNA transfection. In addition, we also found that ENG siRNA inhibited TGF-β-induced phosphorylation of Smad2/3 and Smad1/5/9 in HPMCs treated with high glucose (HG). Conclusion: Our findings confirmed for the first time that endoglin exacerbated PF by regulating the activation of TGF-β/ALK/Smads signaling, which will provide a novel potential therapeutic target in PF.